The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1128/aem.00865-06
|View full text |Cite
|
Sign up to set email alerts
|

Role of Branched-Chain Fatty Acids in pH Stress Tolerance in Listeria monocytogenes

Abstract: In alkaline conditions, Listeria monocytogenes cells develop higher proportions of branched-chain fatty acids (FAs), including more anteiso forms. In acid conditions, the opposite occurs. Reduced growth of pH-sensitive mutants at adverse pH (5.0/9.0) was alleviated by the addition of 2-methylbutyrate (an anteiso-FA precursor), suggesting that anteiso-FAs are important in adaptation to adverse pH. The balance between anteiso-and iso-FAs may be more important than changes in the amounts and/or degrees of saturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
88
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 51 publications
(39 reference statements)
6
88
0
2
Order By: Relevance
“…Anteiso-BCFA have been associated with resistance against environmental stresses in L. monocytogenes (1,11,27). Early in RAW 264.7 macrophage infections, we observed that deficiencies in anteiso-BCFA resulted in a marked loss of intracellular CFU ( Fig.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Anteiso-BCFA have been associated with resistance against environmental stresses in L. monocytogenes (1,11,27). Early in RAW 264.7 macrophage infections, we observed that deficiencies in anteiso-BCFA resulted in a marked loss of intracellular CFU ( Fig.…”
Section: Discussionmentioning
confidence: 64%
“…In this study, we aim to elucidate the contribution of anteiso-BCFA during L. monocytogenes intracellular infection by utilizing the previously characterized cld-2 transposon insertion mutant (1,11,15,26,27) and two independently transduced BKD-deficient mutants in which the cld-2 transposon insertion was transduced into a clean wild-type (WT) background. We show that anteiso-BCFA facilitate intracellular infection of L. monocytogenes by enhancing survival, growth, and phagosomal escape.…”
mentioning
confidence: 99%
“…Previously, we reported that during growth under acidic conditions, S. mutans alters its membrane fatty acid composition by increasing the proportion of unsaturated fatty acids (19,20). Changes in the proportion and type of membrane fatty acid are a common bacterial response to environmental stress (25,27,49). The changes in membrane composition in S. mutans are essential for survival of acid stress, since the inability to incorporate unsaturated fatty acids leads to extreme acid sensitivity and decreased virulence in the rat model of caries (22).…”
Section: Methodsmentioning
confidence: 99%
“…Also, in alkaline conditions, L. monocytogenes cells develop higher proportions of branched-chain fatty acids, including more anteiso forms that are important in adaptation to adverse pH (Giotis et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%